PENGARUH KECERDASAN EMOSIONAL DAN DUKUNGAN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Suwandewi, Ni Kadek Nita; Dewi, I Gusti Ayu Manuati (E-Jurnal Manajemen; Vol 5 No 6 (2016), 2016)
This study aims to analyze the effect of emotional intelligence and organizational support to the organizational citizenship behavior. This research was conducted in cooperation Giri Partners with a total sample of 50 employees who were determined by purposive non-probability sampling techniques. Data collected through interviews and questionnaires. The analysis technique used is multiple linear regression. Based on the analysis found that emotional intelligence and organizational support simultaneous positive and significant impact on OCB. This shows that the higher the emotional intelligence and perceived organizational support of employees, the higher OCB employee. Emotional intelligence is partially positive and significant impact on OCB. This suggests that the ability to motivate self and self-awareness of employees to improve the behavior of OCB. Organizational support is also partially positive and significant impact on OCB. This proves that the support of organizations like treatment of fair organization and organizational will listen to complaints of employees, thereby increasing employee OCB.
Keywords: emotional intelligence, organizational support, organizational citizenship behavior